Multifunctional roles of the mammalian CCR4–NOT complex in physiological phenomena - Shirai, Yo-Taro; Suzuki, Toru; Morita, Masahiro; Takahashi, Akinori; Yamamoto, Tadashi (Frontiers in Genetics, 2014)
The CCR4-NOT complex serves as one of the major deadenylases of eukaryotes. Although it was originally identified and characterized in yeast, recent studies have revealed that the CCR4-NOT complex also exerts important functions in mammals, including humans. However, there are some differences in the composition and functions of the CCR4-NOT complex between mammals and yeast. It is noteworthy that each subunit of the CCR4-NOT complex has unique, multifunctional roles and is responsible for various physiological phenomena. This heterogeneity and versatility of the CCR4-NOT complex makes an overall understanding of this complex difficult. Here, we describe the functions of each subunit of the mammalian CCR4-NOT complex and discuss the molecular mechanisms by which it regulates homeostasis in mammals. Furthermore, a possible link between the disruption of the CCR4-NOT complex and various diseases will be discussed. Finally, we propose that the analysis of mice with each CCR4-NOT subunit knocked out is an effective strategy for clarifying its complicated functions and networks in mammals.